Sistem Informasi Pelayanan Publik Berbasis Web Pada BP2JK Wilayah Jambi - Prihatin, Joko; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2022)
The BP2JK (Balai Pelaksana Pemilihan Jasa Konstruksi) Jambi operates a public service on construction manpower. The problem is the manual search for personnel information. It is difficult for BP2JK Jambi and public to obtain the profile information and workforce history of those who participated in the tender. The objective design a web-based public service information system at the BP2JK Jambi. The research method uses observation and interview techniques. The system design tool is Unified Modeling Language (UML) and prototype modeling. The result is a web-based public service information system at the BP2JK Jambi office, with a search feature based on name personnel or KTP numbers.